CORRUPTION AND INSTITUTIONAL INTEGRITY: THE CASE OF BANGLADESH - Rashid, Mamun; Johara, Fatema (International Journal of Engineering Technologies and Management Research, 2018)
This paper highlights the view that corruption can be combated if institutional integrity can be put into practice, i.e. ‘institutional integrity’ has been considered as a key strategy to curb corruption. Based on literature review, the authors explain argument in three sections: in the first section, the article focuses on conceptualization of corruption, corruption & institutional integrity. In the second section, the article examines integrity-governance-corruption nexus in Bangladesh. Finally, it outlines initiatives of Government of Bangladesh (GoB) for curbing corruption with concluding remark.